Commissioning and operation of the horizontal test apparatus at SNS. Issue 1 (November 2015) - DeGraff, B; Doleans, M; Hannah, B; Howell, M; Kim, S; Neustadt, T; Saunders, J
Abstract: The Spallation Neutron Source (SNS) at Oak Ridge National Lab (ORNL) has built, commissioned and operated a Horizontal Test Apparatus (HTA) vessel in the Radiofrequency Test Facility (RFTF) test cave. It can be operated at 4.5 K using the independent Cryogenic Test Facility (CTF). The HTA is designed to be a single cavity version of an SNS cryomodule with the ability to demount and replace the cavity. It provides the functionality for testing a single dressed SNS medium or high beta Superconducting Radiofrequency (SRF) cavity. The HTA is currently being used in support of R&D for in-situ plasma processing of the cavity's inner niobium surface. The design and commissioning of the HTA at 4.5 K will be presented as well as results from operating the HTA including cool-down, warm-up and steady state operations. Results from plasma processing a warm SCRF cavity in-between cold HTA tests will also be reported.